(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The history of the creation and publication of I.A. Bunin’s diaries are of interest to literary scholars and textual critics, but the study of their linguistic features is not complete. The diaries of I.A. Bunin as a whole and each separately are a communicative, structural and semantic unity, which is reflected in their composition. While retaining the characteristics common to this genre, Bunin’s diaries are original. The author, for example, rejects the classical methods of syntactic connection of records and sentences in them, freely combines fragments of various topics. The integrity of the entire text is preserved not with the help of interphrasal communication, but with the help of keywords repeated in the text, the predominance of certain lexical and semantic series, which determine a certain coherence, that is, a nonlinear type of connectivity that unites elements of different levels of the text. The characteristic properties of Bunin’s diary entries include the parsimony of linguistic means, the accuracy and detail of the chronotope, incomplete sentences, fragmentation and parceling, an abundance of clarifying comments, inserted constructions. Thus, the architectonics of I.A. Bunin, that is, the division of the text into separate semantic fragments, has both common features inherent in the genre and individual ones. Key words: Bunin, composition, architectonics, temporality, parcelling. DOI 10.18522/1995-0640-2020-4-97-106